2011
DOI: 10.1103/physrevd.84.023002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh energy cosmic ray acceleration in newly born magnetars and their associated gravitational wave signatures

Abstract: Newly born magnetars are good candidate sources of ultrahigh energy cosmic rays. These objects can in principle easily accelerate particles to the highest energies required to satisfy the ultrahigh energy cosmic ray scenario (E ∼ 10 20−21 eV), thanks to their important rotational and magnetic energy reservoirs. Their acceleration mechanism, based on unipolar induction, predicts however a hard particle injection that does not fit the observed ultrahigh energy cosmic ray spectrum. Here we show that an adequate d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 76 publications
(139 reference statements)
1
33
0
Order By: Relevance
“…, (18) where S and S ′ denote UHECR sources and sources randomly distributed following selection effects of the catalog of the source candidates. S ′ is isotropically distributed in the entire sky in this study because of the correction of selection effects (see Section 2.4).…”
Section: Statistical Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…, (18) where S and S ′ denote UHECR sources and sources randomly distributed following selection effects of the catalog of the source candidates. S ′ is isotropically distributed in the entire sky in this study because of the correction of selection effects (see Section 2.4).…”
Section: Statistical Quantitiesmentioning
confidence: 99%
“…In either case, the maximum energy of 10 20 eV can only be achieved in extreme environments [1]. Prominent source candidates suggested so far include active galactic nuclei (AGN) [2,3,4,5,6,7,8,9,10], gamma-ray bursts (GRBs) [11,12,13,14], neutron stars or magnetars [15,16,17,18] and clusters of galaxies [19,20,21]. If UHECRs with energies above ∼ 6 × 10 19 eV are mainly protons, their propagation distance should be limited by interactions with cosmic microwave background (CMB) photons [22,23,24,25,26], the so-called Greisen-Zatsepin-Kuz'min (GZK) mechanism, so that they are observable only from sources sufficiently nearby (typically 200 Mpc).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] have also suggested that jetted TDEs may lead to hard spectra.Even if hard spectra production were achieved at each source, it is likely that the overall diffuse UHECR spectrum softens through the integration over the population of sources. Indeed, sources with milder characteristics, which will produce lower-energy particles, are more numerous, and the distribution of their parameters will naturally soften the spectrum [40,41]. A hard spectrum production is thus difficult to justify from a source population point of view.The suppression of the low-energy part of the UHECR spectrum due to the diffusion of low-energy particles in extragalactic magnetic fields, the magnetic horizon effect, has been proposed as a solution to this problem [42,43].…”
mentioning
confidence: 99%
“…Despite decades of observations and modelling (see e.g. Kotera 2011;Abbasi et al 2012 andAloisio 2018 for recent reviews) the underlying source remains uncertain.…”
Section: Ultra-high Energy Cosmic Raysmentioning
confidence: 99%